Promoting Safety of Medicines for Children. - WHO (World Health Organization, 2007)
Monitoring the safety of medicine use in children is of paramount importance since during the clinical development of medicines only limited data on this aspect are generated through clinical trials. Use of medicines outside the specifications described in the licence - in terms of formulation, indications, contraindications or age - constitutes off-label and off-licence use and these are a major area of concern."Promoting Safety of Medicines for Children" is intended to improve awareness of medicine safety issues among those with an interest in the safety of medicines in children and to provide guidance on effective systems for monitoring medicine safety in the paediatric populations. This publication will be of interest to all health care professionals, medicine regulatory authorities, pharmacovigilance centres, academia, the pharmaceutical industry, and policy-makers.